2020
DOI: 10.1002/cre2.335
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dental complications post‐dental treatment in patients with sickle cell disease

Abstract: Objective Our aim was to explore potential medical or dental indicators associated with dental complications and the utilization of emergency services in sickle cell disease (SCD), especially that clinical reports on adverse outcomes post‐dental treatment are scarce. Materials and methods A retrospective analysis of dental treatments of 47 eligible adults with confirmed SCD between May 2016 and October 2019. Logistic regression analysis was used whether clinical outcomes, course of dental treatment, and regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
4
0
3
Order By: Relevance
“…11,12 An accurate history requires good communication with the patient and guardian along with collaborating with the physician. 13 Even though most of the participants believed that it is crucial to inform a dentist about pregnancy, our study indicated the lack of knowledge in regard to pregnancy and dental care. Similar results were reported in the literature among females.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…11,12 An accurate history requires good communication with the patient and guardian along with collaborating with the physician. 13 Even though most of the participants believed that it is crucial to inform a dentist about pregnancy, our study indicated the lack of knowledge in regard to pregnancy and dental care. Similar results were reported in the literature among females.…”
mentioning
confidence: 64%
“… 11 , 12 An accurate history requires good communication with the patient and guardian along with collaborating with the physician. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Os profissionais da odontologia devem ser capazes de reconhecer e tratar pacientes com doença falciforme, conhecendo as manifestações dentárias, e as consequências da doença devem ser consideradas antes do início do tratamento odontológico 4 . O cirurgião dentista deve estar atento aos pacientes com doença falciforme que relatam dores de dente sem causa específica, logo as medidas preventivas são importantes para melhorar a saúde bucal e diminuir significativamente os riscos de infecção 25 .…”
Section: Discussionunclassified
“…As complicações odontológicas são de grande importância, pois ter uma infecção dentária complicada por uma crise falciforme aumenta significativamente a probabilidade de admissão hospitalar entre pacientes adultos com doença falciforme 4 . Baseado nas buscas feitas na literatura, as manifestações bucais encontradas nesses pacientes incluem hipomineralização do esmalte e da dentina, alterações no crescimento e desenvolvimento do complexo maxilomandibular, com tendência à protrusão maxilar, má-oclusão e apinhamento dentário anterior [5][6][7][8][9] , erupção dentária tardia, palidez da mucosa bucal, necrose pulpar assintomática devido a hipóxia existente e destruição do sistema microvascular dentes saudáveis, alterações no trabeculado ósseo 3,[7][8][9][10][11] , atrofia das papilas da língua, áreas radiopacas vistas na radiografia de maxila e mandíbula, dor orofacial 10,11 , osteomielite mandibular, alterações esqueléticas craniofaciais 11 , hiperplasia medular e espaçamento do trabeculado ósseo 3 .…”
Section: Introductionunclassified
“…e application of the immediate installation technique has the advantage of achieving satisfactory results with a high success rate. e use of this technique reduces the number of surgical interventions and shortens the time between tooth extraction and permanent installation of the prosthesis, eventually avoiding the process of bone resorption, thereby leading to the preservation of alveolar ridge in terms of proportion, size, and width [38].…”
Section: Dental Implantsmentioning
confidence: 99%